Analisis Ekstrakurikuler Kepramukaan terhadap Pembentukan Karakter Disiplin Siswa Kelas 6 di Sekolah Dasar Islam Miftahul Ulum Surabaya - Muhammad Wahzudi; Mukhammad Wahyudi; Sevilla Dian Mumtaz (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2026)
The purpose of this study was to examine the impact of scouting activities on the discipline of sixth-grade students at SDI Miftahul Ulum Surabaya. The method used was a qualitative approach, collecting data through interviews, observation, and documentation. Data analysis was carried out in three steps: data reduction, data presentation, and drawing conclusions. The research findings showed that the activities were interesting and enjoyable, which were the main reasons students chose to join scouting activities. The positive impacts of scouting activities include character building, increased discipline, and self-confidence. However, there are also negative effects such as increasing physical and mental stress, triggering conflict between students, and reducing enthusiasm for learning. This study recommends schools, supervisors, and teachers to implement clear rules and provide positive examples as role models for students. As a result, students tend to imitate the examples shown by their leaders. This study aims to comprehensively examine the impact of extracurricular scouting activities on the formation of sixth-grade student discipline at SDI Miftahul Ulum Surabaya. The method used was a descriptive qualitative approach, collecting data through interviews, observation, and documentation. Data analysis was carried out in three steps: data reduction, data presentation, and drawing conclusions. The research findings indicate that engaging and enjoyable activities are the primary reasons students choose to join the Scouts. Positively, Scouts have been shown to foster discipline through routine training, camps, and the General and Special Proficiency Medal (TKU) award system. However, the study also identified negative effects, including physical and mental fatigue, which can diminish academic enthusiasm and trigger potential intragroup conflict due to inter-group competition. Therefore, this study recommends that schools and instructors manage the activity load, implement measurable rules, and prioritize role models to foster discipline without compromising students' psychological well-being.